ANALISA END USER LICENSE AGREEMENT (EULA) SEBAGAI BENTUK PERJANJIAN BAKU DALAM APLIKASI WON by BWS: Analysis Of End User License Agreement (Eula) As A Standard Agreement In WON By BWS Application - Purwanto, Hari (Fakultas Hukum, Universitas Trisakti, 2024)
The WON by BWS application is a form of digital banking product that allows Customers/Users to access banking services directly (real-time) and without the need for face-to-face interaction at the Bank's office. Banking services provided in the WON by BWS application include account opening, transfers in Indonesian Rupiah and US Dollar (both to accounts within BWS and to accounts in other banks), US Dollar purchases (USD-IDR and IDR-USD), bill payments (e.g., credit cards, electricity, telephone bills, etc.), purchases (e.g., flight tickets, phone credit, internet data, etc.), electronic money top-up (OVO, Gopay, ShopeePay), ATM/Debit Card blocking, and other features. Customers/Users intending to use the WON by BWS application are required to understand and agree to the end user license agreement (EULA) established by the Bank, which is a standard agreement as regulated by the Financial Services Authority. BWS, in drafting a standard agreement, must ensure a balance, fairness, and reasonableness between the Bank and Customers/Users. Based on this, the author intends to analyze the end user license agreement (EULA) of the WON by BWS application, to determine whether the standard agreement provides legal protection for Customers/Users.